THE INFLUENCE OF THE USE THE FIRST LANGUAGE IN INDONESIAN EFL CLASSROOMS - Ida Nuraida (Journal of English Language Teaching and Literature (JELTL), 2019)
Despite widespread use only English in Teaching EFL, the use of first language in EFL class has been a perennial topic of discussion in the field of language education. Most established L2 teaching methods discourage the use of L1 in class. This research attempt to explore the use of first language in Indonesian in the EFL Classroom as well as lecturer and students response toward it. The presents study aimed to find out how the lecturer view first language in language classrooms. This research use experimental methods and to take the sample is use random sampling, The objective of the research includes2 Indonesian EFL Lecturer and 48Indonesian EFL students at first semester of teacher training education faculty in Banten Jaya University. The process to gate the data through the interview and questionnaires. The research finding had good result, indicated that English language give the positive response for the students. The resultalso emphasizing to the comprehension the meaning of English language